2020
DOI: 10.1016/j.jaad.2020.06.986
|View full text |Cite
|
Sign up to set email alerts
|

Experience in patients with hidradenitis suppurativa and COVID-19 symptoms

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…It has been postulated that patients with HS are at higher risk for adverse COVID-19 outcomes; 2 however, this has not been previously demonstrated. Lima et al 3 conducted a medical records analysis (although without matching) and did not show increased risk of hospitalization, intensive care admission or death due to COVID-19 in patients with HS versus those without; while Galán et al 4 reviewed the records of 75 HS patients and observed no severe COVID-19 cases or deaths in a region heavily affected at the time. Similarly, in our analysis, outcomes of COVID-19 were not significantly different between patients with and without HS after matching.…”
mentioning
confidence: 99%
“…It has been postulated that patients with HS are at higher risk for adverse COVID-19 outcomes; 2 however, this has not been previously demonstrated. Lima et al 3 conducted a medical records analysis (although without matching) and did not show increased risk of hospitalization, intensive care admission or death due to COVID-19 in patients with HS versus those without; while Galán et al 4 reviewed the records of 75 HS patients and observed no severe COVID-19 cases or deaths in a region heavily affected at the time. Similarly, in our analysis, outcomes of COVID-19 were not significantly different between patients with and without HS after matching.…”
mentioning
confidence: 99%
“…Existing literature on this topic is limited by lack of control groups, which are necessary to identify differences in risk of severe COVID-19 outcomes for patients with HS. [6][7][8][9][10] Our observations have relevance to HS patients and their doctors, who may emphasize exposure mitigation strategies as well as vaccination and boosters for COVID-19.…”
mentioning
confidence: 80%
“…Interestingly, the majority of these COVID‐19 patients were not treated with systemic therapy for HS and no specific risk factors were identified. Meanwhile, only eight cases of mild COVID‐19 occurred in a cohort of 75 Spanish patients 3 and no cases of COVID‐19 occurred among a cohort of 96 Italian patients. 4 This prompted us to investigate why the incidence of COVID‐19 is so low in the HS population and whether there are any risk factors that could increase susceptibility to COVID‐19.…”
mentioning
confidence: 92%